Endothelin-1–Endothelin receptor B complex contributes to oligodendrocyte differentiation and myelin deficits during preterm white matter injury - Du, Mengjie; Wang, Na; Xin, Xiaolong; Yan, Chun-Lan; Gu, Yan; Wang, Liang; Shen, Ying (Frontiers in Cell and Developmental Biology, 2023)
Preterm cerebral white matter injury (WMI), a major form of prenatal brain injury, may potentially be treated by oligodendrocyte (OL) precursor cell (OPC) transplantation. However, the defective differentiation of OPCs during WMI seriously hampers the clinical application of OPC transplantation. Thus, improving the ability of transplanted OPCs to differentiate is critical to OPC transplantation therapy for WMI. Here, we established a hypoxia-ischemia-induced preterm WMI model in mice and screened the molecules affected by WMI using single-cell RNA sequencing. We revealed that endothelin (ET)-1 and endothelin receptor B (ETB) were a pair of signaling molecules for the interaction between neurons and OPCs, and that preterm WMI led to an increase in the number of ETB-positive OPCs and premyelinating OLs. Furthermore, the maturation of OLs was reduced by knocking out ETB, but promoted by stimulating ET-1/ETB signaling. Our work reveals a new signaling module for neuron-OPC interaction and provides new insight for therapy targeting preterm WMI.